2019
DOI: 10.1016/j.esxm.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity the Night Before Exercise Does Not Affect Various Measures of Physical Exercise Performance

Abstract: Introduction The idea that sexual activity can affect athletic performance has been a matter of conjecture for the past several decades. Aim To provide preliminary data on whether sexual activity the evening before several physical exercise performance tests affects performance the next day. Methods Eight participants (mean age, 28 ± 5 years) underwent several physical exercise performance tests on 3 different mornings, under 3 conditions: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In terms of energy expenditure by healthy participants, the studies reported results variously as kcal, METs, and VO 2 reached during the activity. For example, one study found that sexual intercourse expended an average of ~ 130 kcal (Zavorsky et al, 2019 ). Another study found that this energy expenditure was greater in men (~ 101 kcal or ~ 6 METs) than in women (~ 69.10 kcal or ~ 5.60 METs) (Frappier et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of energy expenditure by healthy participants, the studies reported results variously as kcal, METs, and VO 2 reached during the activity. For example, one study found that sexual intercourse expended an average of ~ 130 kcal (Zavorsky et al, 2019 ). Another study found that this energy expenditure was greater in men (~ 101 kcal or ~ 6 METs) than in women (~ 69.10 kcal or ~ 5.60 METs) (Frappier et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…When it came to healthy participants, the peak heart rates during sexual intercourse ranged from ~ 145 bpm (Zavorsky et al, 2019 ) to ~ 170 bpm (Bartlett, 1956 ). There were two studies that analyzed the heart rate pattern during the activity and both agreed that the heart rate increases progressively from foreplay to orgasm, with an average in men of between ~ 96 bpm (Xue-Rui et al, 2008 ) and ~ 127 bpm (Bohlen et al, 1984 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations